Healthy Eating: Create Your Plate! - Jennifer Hillan; Linda B. Bobroff (EDIS)
Meal planning can help you control portion sizes and the amount of carbohydrates you eat throughout the day. This is especially important if you have diabetes or if you are at risk for the disease. The way you ‘create your plate’ to balance carbohydrates for blood glucose control is a bit different from the MyPlate recommendations. Let’s get started with this revised 2-page fact sheet was written by Jennifer Hillan and Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, August 2011.